The Third Reich at war : how the Nazis led Germany from conquest to disaster - Evans, Richard J. 1947- (Penguin Books, 2009)
In 1939 Hitler mobilized Germany into all-out war. This book conjures up a whole society plunged into conflict - from generals and front-line soldiers to Hitler Youth activists and middle-class housewives - tracing events from the invasion of Poland and the Battle of Stalingrad to Hitler's plans for genocide and his eventual suicide, In 1939 Hitler mobilized Germany into all-out war. Richard Evans' astonishing, acclaimed history conjures up a whole society plunged into conflict - from generals and front-line soldiers to Hitler Youth activists and middle-class housewives - tracing events from the invasion of Poland and the Battle of Stalingrad to Hitler's plans for genocide and his eventual suicide. "The Third Reich at War" is a historical masterpiece, showing how Germany rushed headlong into destroying itself and an entire continent